Integrasi Modal Manusia, Kemampuan Tehnologi Informasi, Inovasi dan Kinerja Orgainasi - Fathorrahman, Fathorrahman; Subhan, Subhan; Rika Syahadatina (Jurnal Riset Akuntansi, 2024)
Human capital, capabilities, innovation, organizational performance. This research aims to determine the influence of human capital on IT capabilities, IT capabilities on innovation, and innovation and capabilities on organizational performance. This research is quantitative and descriptive. The data used is primary data obtained through a survey in the form of a questionnaire against regional government organizations in the Pamekasan Regency. The sampling technique uses convenience sampling. This study took a sample of 180 by considering questionnaires that were not returned and were incomplete. The samples analyzed were 165 samples. Data analysis techniques use outer model and inner model testing. Human capital hurts ability, ability has a negative effect on innovation, innovation has a negative effect on organizational performance, and ability has a negative effect on organizational performance.